ASAS ITIKAD BAIK SEBAGAI ALASAN PENOLAKAN GUGATAN OLEH PENGADILAN NIAGA DALAM GUGATAN PEMBATALAN MEREK TERDAFTAR - Lumban Gaol, Selamat (LPPM Universitas Ekasakti Padang, 2022)
The principle of good faith is a fundamental legal principle in the registration and protection of registered trademarks, so it can be a reason for rejecting a lawsuit to cancel a registered trademark in the Commercial Court, if the Plaintiff cannot prove that the registration of the disputed trademark was carried out by the Defendant in bad faith. This article will examine how good faith is regulated in trademark registration based on the 2016 Trademark Law?, and what requirements must be met when filing a lawsuit for canceling a registered mark in the Commercial Court?, as well as how to apply the principle of good faith as a reason for rejecting a lawsuit for canceling a registered mark by the Court. Commerce? This article is the result of normative legal research, using a statutory, case and concept approach, using secondary data, with qualitative data analysis. The research results show that the regulation of good faith is regulated in Article 21 paragraph (3) and Article 77 paragraph (2) of the 2016 Trademark Law, and the requirements that must be fulfilled in filing a lawsuit for cancellation of a registered trademark at the Commercial Court meet the formal and material requirements in Article 76 to Article 79 and Articles 85 to Article 90 Jo. Article 21 of the 2016 Trademark Law, as well as the application of the principle of good faith as a reason for rejecting a claim for cancellation of a registered mark by the Commercial Court, is casuistic and proportional and objective according to the legal facts revealed in the trial.